STRATEGI PENGELOLAAN KABUPATEN SAMOSIR SEBAGAI DAYA TARIK WISATA ALAM DI PROVINSI SUMATERA UTARA - Pardede, Fransiska Roslila Eva Purnama; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 4 No 1 (2016): VOL 4, NO 1 (2016): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i01.p03, 2016)
Abstract Samosir is the only island located in the middle of Lake Toba, one of the largest lakes in the province of North Sumatra. The purpose of this study was to determine the potential of Samosir Island as one of the natural attractions in the province of North Sumatra and know how management strategy that uses SWOT analysis techniques. The data used by the authors in this study a qualitative data. Data was collected by observation, interview and interview. From these data were then analyzed by qualitative descriptive way, the data that is formed into a description that describes a situation or event that are explained. Based on the results of the analysis of the strategic plan management strategies Samosir Island as one of the natural attractions in the province of North Sumatra can be explained as follows: Conducting training in the form of training or training in order to improve the quality of human resources and community knowledge about tourism, tourism promotion Improve both in print media and online media , in cooperation with the travel or travel agency, improve and increase the maintenance of facilities and infrastructure to boost tourist arrivals.
Keywords: Strategy Management, Tourism Potential